2018
DOI: 10.1016/j.jams.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Energy Imbalance of the Meridians in Patients with Temporomandibular Dysfunction

Abstract: Temporomandibular dysfunction (TMD) is a set of changes that affects the muscles of mastication, temporomandibular joint, teeth, and associated periodontal and orofacial structures. According to Traditional Chinese Medicine, the imbalance of energy (Qi) circulating in the acupuncture meridians is always the primary etiologic cause of any physical manifestation. The aim of this study was to describe the patterns of Qi imbalance in patients with TMD by means of an objective measurement. The clinical study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…However, a mysterious phenomenon that has attracted scientific attention for ages has been the fact that, even though acupuncture has enjoyed thousands of years of success, no solid scientific explanation has been proposed for the anatomical pathways of the meridian system (Zhou & Benharash, 2014). It has even been suggested that the meridians themselves do not have a dedicated anatomical structure (Rasera Zotelli et al, 2018; Kovich, 2019). Some scientists do not accept acupuncture, primarily because the meridian system lacks a physical anatomical basis.…”
Section: Introductionmentioning
confidence: 99%
“…However, a mysterious phenomenon that has attracted scientific attention for ages has been the fact that, even though acupuncture has enjoyed thousands of years of success, no solid scientific explanation has been proposed for the anatomical pathways of the meridian system (Zhou & Benharash, 2014). It has even been suggested that the meridians themselves do not have a dedicated anatomical structure (Rasera Zotelli et al, 2018; Kovich, 2019). Some scientists do not accept acupuncture, primarily because the meridian system lacks a physical anatomical basis.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the characteristics of being active, hot, bright, and functional belong to yang; the characteristics of being static, cold, dark, and organic belong to yin, and are considered two opposite energies that we call Qi 15 . Qi is an invisible immaterial substance that circulates in our body through energy channels called meridians 16 . Disease for TCM is the state of imbalance that can manifest as a deficiency or excess of Qi 15 .…”
Section: Introductionmentioning
confidence: 99%
“…An objective way to measure Qi may be performed by the Ryodoraku method, which consists in analysing the existence of electrical conductance in specific points of the skin (source point -high concentration of Qi), like the path of the main meridians of acupuncture (12 on each side of the body) 16 . By measuring the conductivity of each meridian, we can verify energetic excesses or deficiencies 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation